관절경 하 미세골절술 이후에도 통증이 지속되는 거골의 내측 골연골병변에 대하여 이차 관절경 수술과 함께 시행된 과상부절골술: 증례 보고 - 송태훈; 서진수; 최준영; Tae Hun Song; Jin Soo Suh; Jun Young Choi (대한족부족관절학회지, 2023)
A medial opening wedge supramalleolar osteotomy (SMO) introduced by Takakura et al. is a useful realignment procedure for patients with ankle joint arthritis and varus malalignment by shifting the weight-bearing axis laterally and redistributing the loads on the ankle joint. When pain persists after arthroscopic microfracture in patients with medial osteochondral lesion of the talus (OLT), redo arthroscopy, osteochondral autograft transplantation, autologous chondrocyte implantation, or matrix-induced chondrogenesis might be indicated. On the other hand, there is insufficient scientific evidence for realignment surgery through SMO, while the effect of realignment surgery has been studied consecutively for osteochondral lesions of the knee. Therefore, this paper reports a patient with medial OLT who underwent redo arthroscopy combined with SMO for persistent pain after primary arthroscopic microfracture.